Uporaba metode spektralnega razbitja grafov za zasnovo merilnih območij v vodovodnem omrežju - Kozelj, Daniel (Acta hydrotechnica, 2017)
One of the major challenges in managing water supply systems is the high percentage of non-revenue water, wherein the largest contributor is the actual loss of water. In order to decrease the volume of the non-revenue water, district metered areas (DMAs) are introduced, where hydraulic parameters such as pressure and flow are measured. Dividing water distribution systems into different DMAs allows the water management to identify water losses and effective control over the whole system more quickly. We present a method for partitioning complex networks, which uses the algorithm for spectral partitioning of a graph. In order to generate hydraulically suitable solutions also hydraulic input data was also used. The proposed method was tested on a real case study.
Keywords: algoritem; algorithm; district metered areas; graph theory; merilna območja; spectral partition; spektralno razbitje; teorija grafov; vodovodni sistemi; water supply system